Prevalence of lymphatic filariasis in a tea garden worker population of Dibrugarh (Assam), India after six rounds of mass drug administration - A M Khan; P Dutta; C K Sarmah; N K Baruah; S Das; A K Pathak; P Sarmah; M E Hussain; J Mahanta (Journal of Vector Borne Diseases, 2015)
Background & objectives: Lymphatic filariasis (LF) is endemic in the state of Assam and mass drug administration (MDA) programme for LF elimination is being implemented in the state since 2004. A study on prevalence of microfilaria (mf), disease endemicity and vector infection was carried out in a tea garden population of Dibrugarh, Assam (India) to assess the effect of ongoing MDA programme on elimination of LF. Methods: Finger prick thick blood smears (20 mm3) were made from individuals aged ≥2 yr old during night blood survey in between 2000-0000 hrs during the period of November 2012 to February 2013. Blood smears were dehaemoglobinised, stained with Giemsa and examined under microscope for presence of mf. Indoor resting mosquitoes were collected during 0600-1000 hrs and female Culex quinquefasciatus were dissected and examined under microscope for larval forms of the parasite. Results: A total of 634 blood smears were collected and screened for mf and 47 (7.41%) individuals were found microfilaraemic, with predominance of males (74.5%). Highest mf rate (20.0%) was seen in the males of 30-39 yr age group while in females, age group of 10-19 yr recorded maximum mf rate (5.48%). Entomological collection and dissection of Cx. quinquefasciatus revealed presence of larval stages of the parasite and infection and infectivity rates recorded were 13.20 and 3.70%, respectively. Chronic clinical manifestations in the form of elephantiasis and hydrocele were recorded in 33 (5.73%) subjects of the 575 examined. Interpretation & conclusion: Mass drug administration data showed six rounds of MDA with drug distribution coverage in between 63.42 and 95.93% in the study population. Out of 634 individuals examined 47 were found microfilaraemic giving an overall infection rate of 7.41%. Mosquito vector infection and infectivity rates were 13.20 and 3.70%, respectively. Presence of high mf rate, vector infectivity rate and clinical cases in the study population after six rounds of MDA warrants concerted efforts to be made for effective implementation and monitoring of MDA for success of LF elimination programme.